Challenges For Female Teachers At Secondary Level And Its Impact On Students - Sehr Mehmood; Farkhanda Tahir; Sahira Kiran; Sajid Bashir; Dr. Khalid Mahmood Arif; Rizwana Bashir (Kurdish Studies, 2024)
The study was designed to find out the challenges face by female teachers at secondary level and its impact on students learning in district Faisalabad. Female teachers play a vital role in the teaching and learning process, but they encounter numerous obstacles that hinder their ability to fulfill their responsibilities effectively. This research aimed to investigate the specific challenges faced by female teachers at the secondary level, with a focus on identifying the key barriers that prevent them from making a meaningful impact on the education process. This research paper used descriptive quantitative methodology. The study's findings indicate that female teachers' motivation to teach is dwindling due to the politicization of their appointments, transfers, placements, and promotions, which often prioritize political affiliations over merit. Additionally, female teachers are frequently posted in remote areas, where they face challenges such as inadequate accommodation and transportation. The study also revealed that female teachers are overworked, with excessive teaching loads due to staff shortages in schools, which has severely impacted the teaching and learning process. To address these challenges, the study recommends creating a trustworthy environment, strengthening accountability mechanisms, providing ongoing professional development opportunities and incentives for female teachers, making appointments and promotions based on merit, ensuring adequate staffing in schools, and eliminating political interference.